Perceived key injury risk factors in World Cup alpine ski racing—an explorative qualitative study with expert stakeholders - Spörri, J.; Kröll, J.; Amesberger, G.; Blake, O. M.; Müller, E. (British Journal of Sports Medicine, 2012)
Background: There is limited knowledge about key injury risk factors in alpine ski racing, particularly for World Cup (WC) athletes. Objective This study was undertaken to compile and explore perceived intrinsic and extrinsic risk factors for severe injuries in WC alpine ski racing. Methods: Qualitative study. Interviews were conducted with 61 expert stakeholders of the WC ski racing community. Experts` statements were collected, paraphrased and loaded into a database with inductively derived risk factor categories (Risk Factor Analysis). At the end of the interviews, experts were asked to name those risk factors they believed to have a high potential impact on injury risk and to rank them according to their priority of impact (Risk Factor Rating). Results: In total, 32 perceived risk factors categories were derived from the interviews within the basic categories Athlete, Course, Equipment and Snow. Regarding their perceived impact on injury risk, the experts` top five categories were: system ski, binding, plate and boot; changing snow conditions; physical aspects of the athletes; speed and course setting aspects and speed in general. Conclusions: Severe injuries in WC alpine ski racing can have various causes. This study compiled a list of perceived intrinsic and extrinsic risk factors and explored those factors with the highest believed impact on injury risk. Hence, by using more detailed hypotheses derived from this explorative study, further studies should verify the plausibility of these factors as true risk factors for severe injuries in WC alpine ski racing.